2017
DOI: 10.1007/s00592-017-1077-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional status mediates the association between peripheral neuropathy and health-related quality of life in individuals with diabetes

Abstract: AimsTo examine differences in health-related quality of life (HRQoL) between patients with and without diabetic peripheral neuropathy (DPN), and whether these differences can be explained by functional deficits.MethodsThis was a cross-sectional study of 160 patients with type 2 diabetes mellitus, 80 with DPN and 80 without. Assessments included HRQoL (health utility score derived from EQ-5D-5L), functional status measurements [muscle strength, timed up and go (TUG), five times sit-to-stand (FTSTS), functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 43 publications
1
42
2
2
Order By: Relevance
“…A recent study compared 8,150 patients with diabetes mellitus who underwent foot screening with 8,150 patients who did not, and showed that the risk of both minor (3.5‐fold) and major (25‐fold) amputation was significantly increased in the latter, emphasizing the importance of screening for DPN 18 . In two separate studies from Singapore, the presence of DPN has been associated with a poorer functional status and health‐related quality of life 19,20 .…”
Section: Diabetic Peripheral Neuropathymentioning
confidence: 99%
“…A recent study compared 8,150 patients with diabetes mellitus who underwent foot screening with 8,150 patients who did not, and showed that the risk of both minor (3.5‐fold) and major (25‐fold) amputation was significantly increased in the latter, emphasizing the importance of screening for DPN 18 . In two separate studies from Singapore, the presence of DPN has been associated with a poorer functional status and health‐related quality of life 19,20 .…”
Section: Diabetic Peripheral Neuropathymentioning
confidence: 99%
“…Unfortunately, little is known about the characteristics of individuals least likely to engage in self-care. Previous studies have shown that T2DM patients with low diabetes-treatment-related quality of life are less likely to perform adequate self-management of insulin injections [11], and that functional status plays a role in patients' health-related quality of life [12]. Knowledge of diabetes following therapeutic education [13] predicts diabetes self-management [14] and quality of life is associated with the quality of diabetes care.…”
Section: Introductionmentioning
confidence: 99%
“…This VPT estimate can be considered as an indicator of diabetic neuropathy, which may influence their health-related quality of life, as reported in a study involving patients with and without this illness [24]. Suffering from neuropathy also leads to balance problems and mobility disorders [25,26], and increases the risk of falls [27].…”
Section: Discussionmentioning
confidence: 93%